Audiovisual Resources to Improve Administrative Mangenement in Peruvian Companies - Requejo-Pacheco, Gladys; Surichaqui-Gutierrez, Mercedes; Lara-Castillo, Marlon Alfonso; Valderrama-Romero, Antonio Salomón (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Companies adapted their activities to a new social and work reality since the Covid-19 pandemic. Visual resources are now essential for internal communication as remote work spreads as a new way of working life. We sought to determine if the use of visual resources allows us to improve administrative management and its results. A Likert-type survey was used to know the perception of workers and identify which of the functions can be classified as inadequate and highlight the use of visual resources as tools to improve their performance and achieve their business objectives.